BK Virus Nephropathy: Prevalence, Impact and Management Strategies - Sharma R; Zachariah M (International Journal of Nephrology and Renovascular Disease, 2020)
Rajeev Sharma,1,2 Mareena Zachariah3 1School of Medicine, University of Nevada Las Vegas, Las Vegas, NV, USA; 2Jacobs School of Medicine and Biomedical Sciences, University at Buffalo, Buffalo, NY, USA; 3Department of Nephrology, Wayne State University, Detroit, MI, USACorrespondence: Rajeev SharmaSchool of Medicine, University of Nevada Las Vegas, 1701 W Charleston, Blvd, Las Vegas, NV 89102, USAEmail drsharma.r@gmail.comAbstract: BK virus reactivation as a result of therapeutic immunosuppression following renal transplant can result in BK polyomavirus nephropathy and renal allograft loss. This is a complex and challenging clinical problem with a range of management options and practices reported in literature. The current standard for early diagnosis and treatment is surveillance by measuring viral DNA in blood using qPCR. Immunosuppression reduction is the cornerstone of effective management but is associated with a risk of acute rejection following treatment.Keywords: BK polyomavirus nephropathy, kidney transplant, immune monitoring, treatment, surveillance